Fibroblast Growth Factor-23 and Matrix Extracellular Phosphoglycoprotein Levels in Healthy Children and, Pregnant and Puerperal Women - BEREKET, ABDULLAH; DEMİRCİOĞLU, SERAP; GÜRAN, TÜLAY (KARGER, 2020)
Introduction and Objective: Fibroblast growth factor (FGF-23) and matrix extracellular phosphoglycoprotein (MEPE) are bone-related factors and their role in physiologic conditions and in different life stages are unknown. We aimed to evaluate age- and pregnancy-related changes in MEPE and FGF-23 levels and their correlations with calcium (Ca)-phosphate (PO4) metabolism. Methods: The study population included 96 healthy children (50 females) and 31 women (11 healthy, 10 pregnant, and 10 lactating). Intact FGF-23 (iFGF-23), MEPE, ferritin, parathyroid hormone (PTH), 25-OH vitamin D, alkaline phosphatase (ALP), IGF-I, IGFBP-3 and, Ca, PO4 and creatine (Cre) in serum (S) and urine (U) samples were determined. The renal phosphate threshold (TmPO4/GFR) and z-scores for the parameters that show age-related changes were calculated. Results: Serum iFGF-23 concentrations showed nonsignificant changes with age; however, MEPE decreased with age, reaching the lowest levels after 7 years. Additionally, higher serum MEPE concentrations were observed during pregnancy. Other than ALP, all other examined parameters demonstrated age-related changes. ALP, BUN, S-Cre, and U-Ca/Cre showed puerperal and pregnancy related changes together with MEPE. iFGF-23 was positively correlated with S-PO4 and TmPO4/GFR. MEPE was positively correlated with S-Ca, S-PO4 and TmPO4/GFR and negatively correlated with PTH, IGF-1, and IGFBP-3. Conclusion: Not iFGF-23 but MEPE showed age-dependent changes and was affected by pregnancy. Although, MEPE and iFGF-23 did not correlate with each other, they seem to affect serum and urinary phosphate in the same direction. Additionally, we found evidence that ferritin and growth factors might have a role in serum calcium and phosphate regulation.
Keywords: Fibroblast growth factor-23; Matrix extracellular phosphoglycoprotein; Healthy children; Puerperal women; Pregnancy; Lactation; Bone mineralization; Calcium and phosphate metabolism; DOMINANT HYPOPHOSPHATEMIC RICKETS; PARATHYROID-HORMONE; SERUM PHOSPHORUS; REFERENCE VALUES; PHOSPHATE; FGF23; MEPE; DIETARY; KLOTHO; IRON